The role of ESG in enhancing firm resilience to geopolitical risks: an Eastern European perspective - Mohammad Reyad, Hossain; Ayesha, Momtaj; Iqbal, Mohammed Masum; Zariyawati, Mohd Ashhari (John Wiley and Sons, 2024)
Geopolitical risk (GPR) presents a profound challenge to firms, particularly in regions with persistent political instability. In Eastern Europe, where conflicts like the Russia–Ukraine war heighten uncertainty, firms face immediate financial threats and long-term strategic vulnerabilities. This study examines the impact of GPR on firm performance, focusing on the moderating role of environmental, social, and governance (ESG) practices as a resilience mechanism. Using a comprehensive dataset of 1360 publicly listed firms across Poland, Russia, and Ukraine from 2014 to 2023, the analysis employs a base panel data regression model, followed by a two-step generalized method of moments (GMM) approach to account for endogeneity and ensure robustness. The findings reveal a significant negative relationship between GPR and firm performance, measured by return on assets (ROA). Firms exposed to higher geopolitical risks exhibit weaker profitability. However, firms with stronger ESG performance demonstrate greater resilience, as the GMM results show that ESG engagement moderates the adverse effects of GPR on profitability. This suggests that ESG initiatives enhance adaptive capacity in volatile geopolitical environments. In terms of policy implications, ESG should be promoted as a key strategy for firms operating in politically unstable regions. Governments and regulatory bodies may consider mandatory ESG disclosures and incentivizing sustainability practices to help firms mitigate external risks, improve financial resilience, and attract stable investment. Aligning corporate strategies with global ESG standards is essential to ensuring business sustainability amid ongoing geopolitical threats.